Synthesis and Characterization of New Azo Ligand and Its Co(II), Cu(II), Zn(II) and Ni(II) Complexes - Tuncel, Mehmet (Asian Journal of Chemistry, 2014)
This study describe the synthesis and characterization of new azo ligand, 5-hydroxy-4-(2,4-dihydroxyphenylazo)-2,7-naphthalene disulfonic acid disodium salt (L). The Cu(II), Zn(II), Ni(II) and Co(II) complexes of the azo ligand were prepared and characterized by infrared, UV-visible, 1H and 13C NMR spectra, atomic absorption spectroscopy, mass spectrometry, elemental analyses, thermogravimetric analysis, conductivity and magnetic measurements. The results suggest that the complexes have a 1:1 (metal:ligand) molar ratio, involving mononuclear azo ligand with an ONO donor set. Metal ion uptake studies were conducted with a batch technique. The results indicate that the azo ligand has high thermal stability and good metal extraction capacity.